2018
DOI: 10.1016/j.psyneuen.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inability to suppress the stress-induced activation of the HPA axis during the peripartum period engenders deficits in postpartum behaviors in mice

Abstract: The stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis is normally suppressed during pregnancy. Dysregulation of the HPA axis has been proposed to play a role in postpartum depression. However, direct investigation into the relationship between the HPA axis and postpartum depression has been hindered by the lack of useful animal models. Building on our discovery of a role for the K+/Cl-co-transporter, KCC2, in the GABAergic regulation of CRH neurons in the paraventricular nucleus of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 60 publications
0
63
1
2
Order By: Relevance
“…The CRH-ires-Cre mice are knock-in mice generated in which Cre recombinase expression is driven by endogenous promoter/enhancer elements [ 31 ]. The fidelity of Cre recombinase expression in the BAC CRH-Cre line has recently been questioned [ 28 ], although the reported expression pattern does not match our findings [ 16 , 32 ]. In order to determine whether the BAC CRH-Cre line faithfully targets Cre expression to bona fide hippocampal CRH neurons, we assessed CRH reporter (tdTomato) expression and its colocalization with CRH peptide immunoreactivity in BAC CRH-Cre/Ai9 and CRH-ires-Cre/Ai9 hippocampal sections.…”
Section: Resultscontrasting
confidence: 83%
“…The CRH-ires-Cre mice are knock-in mice generated in which Cre recombinase expression is driven by endogenous promoter/enhancer elements [ 31 ]. The fidelity of Cre recombinase expression in the BAC CRH-Cre line has recently been questioned [ 28 ], although the reported expression pattern does not match our findings [ 16 , 32 ]. In order to determine whether the BAC CRH-Cre line faithfully targets Cre expression to bona fide hippocampal CRH neurons, we assessed CRH reporter (tdTomato) expression and its colocalization with CRH peptide immunoreactivity in BAC CRH-Cre/Ai9 and CRH-ires-Cre/Ai9 hippocampal sections.…”
Section: Resultscontrasting
confidence: 83%
“…We also find psychosocial stressors contribute to the emergence of PPD by interfering with basal and stress-induced peripartum HPA axis adaptations. A recent study found chemogenetic stimulation of PVN CRH neurons to be sufficient to generate deficits in maternal care as well as depressive-like behaviors 89 . Consistent with these findings, our results implicate increased PVN CRH signaling with the emergence of abnormal postpartum behaviors and neuroendocrine function, and further suggest downregulation in PVN nuclear steroid receptors could in part be mediating these effects.…”
Section: Discussionmentioning
confidence: 99%
“…KCC2 FL mice ( Slc12a5 lox/lox ) were have been described previous and have been backcrossed on the C57BL/6 J mice for 10 generations [ 26 ]. PCR was with an expected product size of 426 bp for wild-type and 543 bp for KCC2 FL mice.…”
Section: Methodsmentioning
confidence: 99%